Type inference for GADTs and anti-unification - Gelain A.* (2015)
© Springer International Publishing Switzerland 2015.Nowadays the support of generalized algebraic data types (GADTs) in extensions of Haskell allows functions defined over GADTs to be written without the need for type annotations in some cases and requires type annotations in other cases. In this paper we present a type inference algorithm for GADTs that is based on a closed-world approach to overloading and uses anti-unification and constraint-set satisfiability to infer the relationship between the types of function arguments and result. Through some examples, we show how the proposed algorithm allows more functions defined over GADTs to be written without the need for type annotations.